Some Considerations about the Performance of Terms as a Linguistic-Cultural Unit - Mirhojiddinovna, Jamoliddinova Dilnoza; Nazokat, Kasimova (Researchparks Publishing, 2023)
In the article, the function of linguokulturema in connection with the writing skills of the terms within the artistic text is analyzed with the help of examples. It has been proven that the term lingvokulturema can reflect the national culture and identity characteristic of a nation.